FAKTOR-FAKTOR PENENTU STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN: BUKTI DARI BURSA EFEK INDONESIA TAHUN 2020-2024 - Silviana, Putri; Indriasih, Dewi; Fanani, Baihaqi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The study looks at how capital structure is affected by internal financial characteristics in food and beverage companies listed and registered on the Indonesian Stock Exchange between 2020 and 2024. The elements include effective tax rates, firm size, business risk, sales growth, and non-debt tax shield. Given the strategic importance of capital structure in maintaining financial resilience, the study focuses on the food and beverage industry, which has shown remarkable adaptation during the post-pandemic period.Methods: The annual reports of sixty-three food and beverage companies listed on the Indonesia Stock Exchange provided the secondary data for this quantitative analysis. These yearly reports include 315 company-year observations, are included in these yearly reports, which span the years 2020-2024. In order to meet the normalcy assumption and enhance the validity of the regression model, outliers were found using case-by-case diagnostic techniques prior to regression testing.Results: The results show that business risk significantly and negatively affects capital structure. This implies that companies with more business risk tend to use less funding. Conversely, non-debt tax shield, firm size, sales growth, or effective tax rate are found to have a statistically significant influence on capital structure decisions. Keywords: Business Risk , Capital Structure, Effective Tax Rate, Firm Size, Non-Debt Tax Shield, Sales Growth